PENGUATAN PROFIL PELAJAR PANCASILA MENGGUNAKAN MODEL VALUE CLARIFICATION TECHNIQUE (VCT) TIPE PENGALAMAN DIRI SENDIRI PADA PENDIDIKAN PANCASILA SEKOLAH DASAR - Eningsih, Isna; Buju Basafpipana H, Maha Lastasa; Asmiati, Syarifah (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2026)
This study aimed to describe the strengthening of the Pancasila Student Profile through the implementation of the Value Clarification Technique (VCT) model, specifically the self-experience type, in Pancasila Education at the elementary school level. The research employed a descriptive qualitative method, with data collected through observation, in-depth interviews, and documentation. The subjects were the principal and a second-grade teacher at SD Negeri 03 Pontianak Timur. Data analysis included data collection, reduction, and presentation. The results indicated that the VCT model based on self-experience was effective in enhancing students’ understanding and internalization of Pancasila values. Lesson planning was conducted by developing teaching modules aligned with Pancasila values and applying experience-based learning strategies. The implementation of this model contributed to character development, increased students’ awareness of Pancasila values, and fostered attitudes such as cooperation, independence, and devotion to God. Evaluation was carried out through reflective activities, direct observation, and formative assessments. In conclusion, the VCT model is an effective approach to strengthening the Pancasila Student Profile in elementary education.